Evolution Process of a Broadband Coplanar- Waveguide-fed Monopole Antenna for Wireless Customer Premises Equipment - Alishir Moradikordalivand; Tharek A. Rahman; Ali N. Obadiah; Mursyidul Idzam Sabran (Indonesian Journal of Electrical Engineering and Computer Science, 2014)
In this paper a design process of a broadband printed monopole antenna using stepped cut at four corners (CSFC) technique is proposed. The CSFC is a technique that four corners a patch (rectangular/square) of planar monopole antennas are cut in order to enhance the impedance bandwidth. The technique can be used to design any different types of planar monopole antenna in specific frequency ranges. Therefore, to become more acquaintance with the CSFC technique an evolution process of single band to broadband antenna is represented. However, the proposed antenna is designed for wireless indoor customer premises equipment (CPE) using the coplanar waveguide (CPW) feeding technique. Moreover, the antenna is simulated using CST software and also fabricated and tested so as to validate the results. The simulated and measured -10 dB reflection bandwidth is 104% (850MHz to 2.7 GHz) to cover GSM (900 and 1800 MHz), WiFi (2.4 GHz) and LTE (2.6 GHz) applications. High efficiency and gain as well as omnidirectional and quasi-omnidirectional of radiation pattern at lower and upper frequencies have been achieved.